2022
DOI: 10.3390/fire5060177
|View full text |Cite
|
Sign up to set email alerts
|

Summer and Fall Extreme Fire Weather Projected to Occur More Often and Affect a Growing Portion of California throughout the 21st Century

Abstract: Annual burned area has increased in California over the past three decades as a result of rising temperatures and a greater atmospheric demand for moisture, a trend that is projected to continue throughout the 21st century as a result of climate change. Here, we implement a bias-correction and statistical downscaling technique to obtain high resolution, daily meteorological conditions for input into two fire weather indices: vapor pressure deficit (VPD) and the Canadian Fire Weather Index System (FWI). We focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…These results are consistent with other findings; for instance, [12] spotted vast improvement in the monthly and seasonal rainfall values after bias correcting seasonal forecasts using BCSD method. [34] , recently also recorded similar results in Califonia where seasonal rainfall was well represented post BSCD. During the dry season (DJF), we observed that the BSCD was very good at bias correction, as very high values observed by the raw CHIRPS V2 in the southwestern parts of the country were well corrected to resemble those of the gauge.…”
Section: Resultssupporting
confidence: 68%
“…These results are consistent with other findings; for instance, [12] spotted vast improvement in the monthly and seasonal rainfall values after bias correcting seasonal forecasts using BCSD method. [34] , recently also recorded similar results in Califonia where seasonal rainfall was well represented post BSCD. During the dry season (DJF), we observed that the BSCD was very good at bias correction, as very high values observed by the raw CHIRPS V2 in the southwestern parts of the country were well corrected to resemble those of the gauge.…”
Section: Resultssupporting
confidence: 68%